Residential mobility of middle-class and popular sectors: the city of Buenos Aires as an arrival destination - Cosacov, Natalia (2018)
Fil: Cosacov, Andrea. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.